Health in industry : a growing movement - Mackenzie, James; Haldane, William S.
1927-02-25 1927 1920s 4 pages HEALTH IN INDUSTRY. A GROWING MOVEMENT. Prevention of Occupational Sickness and Disease. The Industrial Health Education Society, an organisation which came into being last year for the purpose of propagating among those engaged in industry throughout Great Britain knowledge of how health may be maintained, held its first annual meeting in the Goold Hall, Edinburgh, on February 25, 1927. The Society had its origin in, and has taken the place of the Industrial Health Education Council, a purely Scottish body with similar aims. Sir William S. Haldane, W.S., presided, and among those who attended were Sir John R. Findlay, Bart., Sir Thomas Oliver, M.D., Newcastle-on-Tyne ; Dr. G. Clark Trotter, F.R.S.E., Medical Officer of Health, Islington, London; Lord Salvesen, Mr. Robert Smillie, M.P., representing the British Trade Union Council, and Mr. Peter Webster, president of the Scottish Trades Union Congress General Council. Sir William Haldane said that was the first annual meeting of the Society, but it was the second annual meeting of those engaged in the united endeavour to combat the evil of ill-health among the industrial classes by the spread of knowledge as to how health was to be maintained. He recalled how the work came to be undertaken. Two years ago some of them in Scotland became alive to the immense extent of preventable sickness, largely of occupational nature, that was not only causing serious loss of time and efficiency among the workers, but was causing widespread suffering and distress. It was reckoned that among insured persons at least. 26 Million Weeks per annum were lost through sickness, not reckoning sickness or disability for which no benefit was payable. Educational methods seemed to them the surest means of enabling the workers to defend themselves from the prevailing evils of ill-health affecting the particular occupations engaged in. They recognised that the evils could be effectively combated only by personal effort and care on the part of the individual, notwithstanding all that was being done by public authorities towards securing healthful conditions of work. It was that appeal to the individual worker, to his intelligence, his sense of personal responsibility, as well as to his own interest, that was the central point of their work, giving him, with the willing help of the medical profession, the guidance which might enable him to steer clear of much preventable suffering and misery. 292/840/1/8